The antibody aducanumab reduces Aβ plaques in Alzheimer’s disease - Sevigny, Jeff; Chiao, Ping; Bussière, Thierry; Weinreb, Paul H.; Williams, Leslie; Maier, Marcel; Dunstan, Robert; Salloway, Stephen; Chen, Tianle; Ling, Yan; O’Gorman, John; Qian, Fang; et al. (Nature (London), 2016)
Alzheimer’s disease (AD) is characterized by deposition of amyloid-β (Aβ) plaques and neurofibrillary tangles in the brain, accompanied by synaptic dysfunction and neurodegeneration. Antibody-based immunotherapy against Aβ to trigger its clearance or mitigate its neurotoxicity has so far been unsuccessful. Here we report the generation of aducanumab, a human monoclonal antibody that selectively targets aggregated Aβ. In a transgenic mouse model of AD, aducanumab is shown to enter the brain, bind parenchymal Aβ, and reduce soluble and insoluble Aβ in a dose-dependent manner. In patients with prodromal or mild AD, one year of monthly intravenous infusions of aducanumab reduces brain Aβ in a dose- and time-dependent manner. This is accompanied by a slowing of clinical decline measured by Clinical Dementia Rating—Sum of Boxes and Mini Mental State Examination scores. The main safety and tolerability findings are amyloid-related imaging abnormalities. These results justify further development of aducanumab for the treatment of AD. Should the slowing of clinical decline be confirmed in ongoing phase 3 clinical trials, it would provide compelling support for the amyloid hypothesis. Aducanumab, a human monoclonal antibody that selectively targets aggregated Aβ, reduces soluble and insoluble Aβ in the brain, an action accompanied by a dose-dependent slowing of clinical decline in treated patients. A prospect for amyloid-β-removal therapy Aducanumab is a recombinant human monoclonal antibody that selectively targets the amyloid-β (Aβ) peptide aggregates thought to play a part in the neurodegenerative process in Alzheimer's disease. Several Alzheimer's disease drugs have failed in development in recent years — including other anti-amyloid antibodies — so there is intense interest in any new developments. A new study reports interim results from a clinical trial of monthly infusions of aducanumab in subjects with prodromal or mild Alzheimer's disease. Treatment with aducanumab reduced brain Aβ plaques, an action accompanied by a dose-dependent slowing of clinical decline. The trial data support further development of aducanumab as an Aβ-removing therapy.